Pengaruh Struktur Kepemilikan, Dewan Komisaris, dan Kebijakan Dividen terhadap Corporate Social Responsibility - Putri Suprijani; Dina Patrisia (Jurnal Kajian Manajemen dan Wirausaha, 2020)
Purpose - This study aims to determine the effect of ownership structure, board of commissioners, and dividend policy on corporate social responsibility of companies listed in the Indonesia Stock Exchange.Methodology - this research is classified as causative research. The populations in this study were all companies listed in the Indonesia Stock Exchange in 2014-2018. The sample in this study was determined by purposive sampling based on the criteria of companies listed in the Indonesia Stock Exchange companies that are consecutively ranked in the Indonesia Stock Exchange  during the 2014-2018. The samples in this study were 87. The type of data used is secondary data from the website www.idx.co.id. The analytical method used is multiple regression analysis using the SPSS program.Finding – the results of this study indicate (1)family ownership has no significant positive effect on corporate social responsibility in companies listed on the Indonesia Stock Exchange (2)foreign ownership has a significant positive effect on corporate social responsibility in companies listed on the Indonesia Stock Exchange (3)meeting frequency of board of commissioners has a no significant positive effect on corporate social responsibility in the Indonesia Stock Exchange (4)independen board of directors has significant positive effect on corporate social responsibility in the Indonesia Stock Exchange (5) dividend payout ratio has no significant positive effect on corporate social responsibility on capital structure in companies listed in the Indonesia Stock Exchange Keywords: Corporate Social Responsibility, family ownership, foreign ownership, dividend payout ratio